Edukasi Pengurangan Emesis Gravidarum melelui Seduhan Zingiber Officinale - Anne Rufaridah; Azkiyaunnisa'; Nurhalimah Juneldi; Lailatul Husni (JURNAL ABDIMAS SERAWAI, 2026)
Pregnancy causes hormonal changes in the body. These changes are due to an imbalance in the hormones progesterone and estrogen. Hormonal changes that occur during pregnancy include increased progesterone and estrogen production, resulting in the production of placental HCG (Human Chorionic Gonadotropin), which causes emesis gravidarum. The influence of estrogen causes increased gastric acid production and excessive salivation (hypersalivation), a burning sensation in the stomach, nausea, vomiting, and headaches, especially in the morning, known as morning sickness. The resulting vomiting is called emesis gravidarum. Excessive, disturbing vomiting is called hyperemesis gravidarum. Several studies have shown that ginger has anti-nausea and anti-vomiting effects. Ginger is a substance that can expel gas from the stomach, which will relieve bloating. Ginger is a powerful aromatic stimulant and can control vomiting by increasing intestinal peristalsis. About six compounds in ginger have been shown to have antiemetic (anti-vomiting) activity. The active ingredients contained in ginger can be used as a non-pharmacological therapy for hyperemesis gravidarum